Analisis Penerapan Akuntansi Berdasarkan Sak EMKM pada UMKM: Warung Seblak Teh Windy - Putri Damayanti; Puji Isyanto; Trias Arimurti (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
MSMEs have a significant contribution, including: increasing employment opportunities and obtaining labor, forming Gross Domestic Product (GDP), and also becoming an option for people with low incomes to carry out productive economic activities. The object of this research is the UMKM Seblak Teh Windy which is located in Karawang Regency. This research aims to obtain information on how Seblak Teh Windy presents financial reports, analyze the accuracy of Seblak Teh Windy's financial accounting process using SAK EMKM, and reconstruct Seblak Teh Windy's financial records based on SAK EMKM. Qualitative methods were used in this research, data collection was carried out through interviews and documentation. The final results stated that Seblak Teh Windy UMKM did not keep financial records in accordance with SAK EMKM, where they only compiled daily expenses and receipts. Therefore, this research produces an analysis of Seblak Teh Windy's financial records in accordance with SAK EMKM, consisting of a financial position report, notes to financial reports and profit and loss reportss.